Information Gathering on a Web Application deployed in Ruby on Rails - Bhardwaj, Harsh; Aggarwal, Manish; Gupta, Neha (International Journal of Computer Sciences and Engineering, 2025)
In this world of providing effective interface to the user for accomplishing the requirements needed to perform information gathering for the purpose of implementing Penetration testing in a network we need an adaptive scenario of carrying out the same task. Ruby on Rails provides an interactive way of dealing with the user’s inputs. This kind of Web application allows a user to perform the basic information gathering, regarding possible threats in its network without having prior knowledge of Penetration testing.